Nitrogen/Carbon-Coated Zero-Valent Copper as Highly Efficient Co-catalysts for TiO2 Applied in Photocatalytic and Photoelectrocatalytic Hydrogen Production - James McGettrick (ACS Applied Materials & Interfaces, 2020)
Zero-valent copper (Cu0) is a promising co-catalyst in semiconductor-based photocatalysis as it is inexpensive and exhibits electronic properties similar to those of Ag and Au. However, its practical application in photocatalytic hydrogen production is limited by its susceptibility to oxidation, forming less active Cu species. Herein, we have carried out in situ encapsulation of Cu0 nanoparticles with N-graphitic carbon layers (14.4% N) to stabilize Cu0 nanoparticles (N/C-coated Cu) and improve the electronic communication with a TiO2 photocatalyst. A facile solvothermal procedure is used to coat the Cu0 nanoparticles at 200 °C, while graphitization is achieved by calcination at 550 °C under an inert atmosphere. The resultant N/C-coated Cu/TiO2 composites outperform the uncoated Cu counterparts, exhibiting a 27-fold enhancement of the hydrogen evolution rate compared to TiO2 and achieving a rate of 19.03 mmol g–1 h–1 under UV–vis irradiation. Likewise, the N/C-coated Cu co-catalyst exhibits a less negative onset potential of −0.05 V toward hydrogen evolution compared to uncoated Cu (ca. −0.30 V). This superior activity is attributed to coating Cu0 with N/C, which enhances the stability, electronic communication with TiO2, conductivity, and interfacial charge transfer processes. The reported synthetic approach is simple and scalable, yielding an efficient and affordable Cu0 co-catalyst for TiO2.